Eighty years later: a new Neotropical species of Megalopelma Enderlein (Mycetophilidae) from the Cerrado and its conservation units - Afiune, Giovana P. S.; Oliveira, Sarah S. (Zootaxa, 2024)
The genus Megelopelma was erected by Enderlein in 1910 for a species from Nova Teutônia district, Seara municipality in Santa Catarina state, Brazil. Edwards, in 1940, added three Neotropical species to the genus and no more species have been described so far, nor with the recent Diptera surveys in the Neotropics, which did not sample the genus. With a distance of more than 1,000 km from the genus type-locality and more than eighty years since the last species was described, we present a new species of Megalopelma from conservation units of Brazilian Cerrado, the central area of the Neotropical region, including photos, a distribution map, and a brief discussion regarding its potential use as a biological indicator for long-term monitoring.